Research on Reconstruction of Historical Buildings: - IGAGA Widiana Kepakisan; Syamsul Alam Paturusi; Ngakan Ketut Acwin Dwijendra; I Dewa Gede Agung Diasana Putra (International Journal of Engineering and Emerging Technology, 2021)
Various research on the reconstruction of historical buildings has been carried out by researchers from various countries. To find out about its progress, it is necessary to use bibliometric analysis to map studies related to the reconstruction of historical buildings. The aim of this study is to highlight high-impact research related to the reconstruction of historical buildings published in international journals. Based on these results, research opportunities related to this topic in the future can be seen. Bibliometric analysis was performed using the VOSviewer application. Data retrieval for articles related to the reconstruction of historical buildings was carried out on the Scopus database and filtered according to the research and language fields which meant that 137 documents were obtained. The results of the study indicate that the number of articles that discuss this topic have exhibited a significant development. The citation of publications related to this topic are from journals rather than conference papers. Furthermore, the country that contributed the most articles was Italy. Finally, research related to this topic can be grouped into four categories with the current trends in research being towards urban planning, office building, masonry materials, history, virtual reconstruction, and sustainable development. The results of this bibliometric study are expected to provide an overview for future researchers to investigate matters that have still not been much discussed in research on the reconstruction of historical buildings.